HUBUNGAN ANTARA MORFOMETRIK DAN BOBOT BADAN DOMBA SAKUB JANTAN DI KABUPATEN BREBES - Nurasih, Ari Dwi; Sumaryadi, Mas Yedi; Hidayah, Chomsiatun Nurul; Nugroho, Aras Prasetiyo; Yuwono, Pambudi; Haryoko, Imbang; Candrasari, Dewi Puspita (ANGON: Journal of Animal Science and Technology, 2022)
Background. Sakub sheep is a local sheep in Brebes Regency, Central Java, that has the potential as a genetic resource because it has a jumbo body. To know the body weight, weighing must be done. However, in buying and selling transactions, body weight can be estimated using livestock body measurements. Livestock body morphometrics such as body length, chest circumference, and shoulder height can be used to estimate livestock body weight. The study aimed to determine whether there is a relationship between body morphometric measures (body length, chest circumference, and shoulder height) and body weight in male sakub sheep. By studying this relationship, we can obtain useful information in optimizing ram production and can assist in determining appropriate management and nutrition strategies to increase ram body weight. Materials and Methods. Sheep were used in several age groups (12 months, 18 months, 24 months, and 36 months). The tools used in this study were hanging scales, measuring tapes, and stationery. Results. Based on the study's results, it can be seen that the relationship between body morphometrics (body length, chest circumference, and shoulder height) and body weight of male sakub sheep in various age groups has differences in the level of correlation. In the 12-month age group, the shoulder height variable had a very strong correlation (0.95) with body weight, while body length had a moderate correlation (0.55) and chest circumference had a low correlation (0.33). In the 18-month age group, the chest circumference variable had a very strong correlation (0.89) with body weight, while body length and shoulder height had strong correlations of 0.79 and 0.74, respectively. At 24 months of age, body length had a very strong correlation with body weight (0.99), while shoulder height had a moderate correlation (0.59) and chest circumference had a low correlation (0.29). In the 36-month age group, body length had a very strong correlation with body weight at 0.99, shoulder height had a strong correlation at 0.72, while the chest circumference variable had a low correlation (0.52). Conclusion. Based on the research and discussion that has been done, it can be concluded that there is a relationship between body morphometrics (body length, chest circumference, and shoulder height) to the body weight of male sakub sheep.